Beyond dropout: A study on BRAC Primary School - Khan, Ashrafuzzaman; Samadder, Mrinmoy (BRAC Research and Evaluation Division, 2022)
This study explored the reasons for dropout of students from BRAC primary schools. Data were collected in two phases through qualitative and quantitative methods. In the first phase, 681 schools were visited to find out the proportion of students dropped out. In the second phase, out of these 681 schools 128 were randomly selected to explore the reasons for dropout. The study was conducted on the schools located in Dhaka and Chittagong cities and in Bandarban and Rangamati districts. The overall dropout rate was 6.13% in the 681 schools visited. The reasons for dropout were grouped under five heads: familial, personal, educational, school- and community-related. Their contributions to dropout were 53.3%, 34.2%, 18.1%, 14.5%, and 14.1% respectively. The incidence of the dropout was higher among the female students and in the urban areas. The dropout in 3rd grade was the highest as the students found their textbooks difficult at that grade. Thus, it was recommended that the textbooks might be revised to make them easier to the students.